The Role of Green Accounting, Good Corporate Governance, and Environmental Performance Corporate Social Responsibility - Taufiq, Abd Rohman; Sanusi, Anwar; Assih, Prihat (Indonesian Journal of Business Analytics, 2024)
The goal of the research is to find out how environmental performance is affected in industrial businesses listed on the IDX between 2017 and 2020 by sustainable accounting and good corporate governance. A manufacturing company with managerial ownership shares for the yearly report and continual involvement in the PROPER program makes up the study's population. Using the SPSS 22 analytic tool, the multiple line regression technique was used to 66 yearly reports as a sample and data processing procedures. The results of this research indicate that, while green accounting is voluntary and has not been fully implemented in the nation of Indonesia, it does have an impact on the nation's environmental performance. Second, environmental performance is affected by the implementation of sound corporate governance.